Photonic crystals with a chiral basis by holographic lithography - Dedman, E; Sharp, D; Turberfield, A; Blanford, C; Denning, R (2005)
We demonstrate the use of holographic lithography to fabricate chiral photonic crystals. These structures are calculated to exhibit strong optical activity even though they are made from material that is not intrinsically optically active. By control of the polarizations of the interfering plane waves that are used to define the three-dimensional inicrostructure it is possible to create left-and right-handed and closely related non-chiral structures. (c) 2005 Elsevier B.V. All rights reserved.